(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The training program "Adaptive AI Integration for Inclusive Learning: Training Prospective Elementary School Teachers" addresses the critical gap in teacher education curricula in Indonesia regarding the integration of adaptive AI technology for inclusive education, particularly for prospective teachers facing challenges in designing adaptive learning for diverse student needs. Conducted with 30 prospective teachers from Cenderawasih University’s PGSD program who were undergoing Field Experience Practice (PPL) in Jayapura, Papua, the training employed a Participatory Rural Appraisal (PRA) method across three systematic stages: preparation, implementation, and reflection. Results demonstrated significant improvements across all competency indicators: conceptual understanding of inclusive learning increased by 62.5% (from 52.4 to 85.2), and 92% of participants successfully explained AI applications for elementary education, with 85% demonstrating practical mastery of at least two adaptive AI features. The program’s key contribution lies in its successful integration of adaptive AI into inclusive education training, producing replicable training modules on "Designing Needs-Based Inclusive Lesson Plans" and "Utilizing Adaptive AI for Inclusive Learning," while fundamentally transforming participants’ perceptions of AI from a potential threat to an empowering educational tool. This model offers a scalable blueprint for Teacher Training Institutions (LPTK) across Indonesia to enhance 21st-century teaching competencies and accelerate the implementation of technology-based inclusive education.